Effect of silica fume and fly ash admixtures on the corrosion behavior of AISI 304 embedded in concrete exposed in 3.5% NaCl solution - Baltazar Zamora, Miguel Ángel; Bastidas, David M.; Santiago Hurtado, Griselda; Mendoza Rangel, José Manuel; Gaona Tiburcio, Citlalli; Almeraya Calderón, Facundo; Bastidas, José María (Molecular Diversity Preservation International, 2019)
The use of supplementary cementitious materials such as fly ash, slag, and silica fume improve reinforced concrete corrosion performance, while decreasing cost and reducing environmental impact compared to ordinary Portland cement. In this study, the corrosion behavior of AISI 1018 carbon steel (CS) and AISI 304 stainless steel (SS) reinforcements was studied for 365 days. Three different concrete mixtures were tested: 100% CPC (composite Portland cement), 80% CPC and 20% silica fume (SF), and 80% CPC and 20% fly ash (FA). The concrete mixtures were designed according to the ACI 211.1 standard. The reinforced concrete specimens were immersed in a 3.5 wt.% NaCl test solution to simulate a marine environment. Corrosion monitoring was evaluated using the corrosion potential (Ecorr) according to ASTM C876 and the linear polarization resistance (LPR) according to ASTM G59. The results show that AISI 304 SS reinforcements yielded the best corrosion behavior, with Ecorr values mainly pertaining to the region of 10% probability of corrosion, and corrosion current density (icorr) values indicating passivity after 105 days of experimentation and low probability of corrosion for the remainder of the test period.